ROSAT PSPC view of the hot interstellar medium of the Magellanic Clouds - Sasaki, Manami; Haberl, Frank; Pietsch, Wolfgang (Astronomy & Astrophysics, 2002)
Diffuse X-ray emission from the Magellanic Clouds (MCs) is studied by using all the archival data of pointed ROSAT Position Sensitive Proportional Counter (PSPC) observations. For this purpose, contributions from the point and point-like sources in the ROSAT High Resolution Imager (HRI) and PSPC source catalogues are eliminated and periods of high solar activity are excluded. The spectral analysis yielded characteristic temperatures of 10(6)-10(7) K for the hot thin plasma of the ISM which extends over the whole Large Magellanic Cloud (LMC) and the Small Magellanic Cloud (SMC). The total unabsorbed luminosity in the 0.1-2.4 keV band within the observed area amounts to 3.2 x 10(38) erg s(-1) in the LMC and 1.1 x 10(37) erg s(-1) in the SMC, each with an uncertainty of similar to -40%, +100%. The X-ray luminosity of the LMC is comparable to that of other nearby galaxies with pronounced star formation. In the LMC, hot regions were found especially around the supergiant shell (SGS) LMC4 and in the field covering SGS LMC2 and LMC3. Highest temperatures for the SMC were derived in the southwestern part of the galaxy. The diffuse X-ray emission is most likely a superposition of the emission from the hot gas in the interior of shells and supershells as well as from the halo of these galaxies.
Keywords: shock waves; ISM : supernova remnants; galaxies : magellanic clouds; X-rays : ISM